Grand Rounds: Asbestos-Related Pericarditis in a Boiler Operator - Abejie, Belayneh A. (National Institute of Environmental Health Sciences, 2008)
CONTEXT: Occupational and environmental exposures to asbestos remain a public health problem even in developed countries. Because of the long latency in asbestos-related pathology, past asbestos exposure continues to contribute to incident disease. Asbestos most commonly produces pulmonary pathology, with asbestos-related pleural disease as the most common manifestation. Although the pleurae and pericardium share certain histologic characteristics, asbestos-related pericarditis is rarely reported. CASE PRESENTATION: We present a 59-year-old man who worked around boilers for almost 30 years and was eventually determined to have calcific, constrictive pericarditis. He initially presented with an infectious exacerbation of chronic bronchitis. Chest radiographs demonstrated pleural and pericardial calcifications. Further evaluation with cardiac catheterization showed a hemodynamic picture consistent with constrictive pericarditis. A high-resolution computerized tomography scan of the chest demonstrated dense calcification in the pericardium, right pleural thickening and nodularity, right pleural plaque without calcification, and density in the right middle lobe. Pulmonary function testing showed mild obstruction and borderline low diffusing capacity. DISCUSSION: Based on the patient’s occupational history, the presence of pleural pathology consistent with asbestos, previous evidence that asbestos can affect the pericardium, and absence of other likely explanations, we concluded that his pericarditis was asbestos-related. RELEVANCE TO CLINICAL PRACTICE: Similar to pleural thickening and plaque formation, asbestos may cause progressive fibrosis of the pericardium.